2020
DOI: 10.1186/s13287-020-01895-1
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell-based cell-free strategies: safe and effective treatments for liver injury

Abstract: Various hepatoxic factors, such as viruses, drugs, lipid deposition, and autoimmune responses, induce acute or chronic liver injury, and 3.5% of all worldwide deaths result from liver cirrhosis, liver failure, or hepatocellular carcinoma. Liver transplantation is currently limited by few liver donors, expensive surgical costs, and severe immune rejection. Cell therapy, including hepatocyte transplantation and stem cell transplantation, has recently become an attractive option to reduce the overall need for liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(59 citation statements)
references
References 102 publications
0
57
0
2
Order By: Relevance
“…Mesenchymal stem cells (MSCs) have a self-renewal capacity and are derived from the bone marrow, adipose tissue, umbilical cord, etc. They are the subject of focus in regenerative medicine and serve as a potential therapy for different liver diseases[ 151 , 152 ]. MSCs were shown to improve liver regeneration in patients with cirrhosis by elevating anti-apoptotic factors, such as HGF and IGF-1, and angiogenic and mitogenic factors.…”
Section: Stimulation Of Insufficient Liver Regenerationmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) have a self-renewal capacity and are derived from the bone marrow, adipose tissue, umbilical cord, etc. They are the subject of focus in regenerative medicine and serve as a potential therapy for different liver diseases[ 151 , 152 ]. MSCs were shown to improve liver regeneration in patients with cirrhosis by elevating anti-apoptotic factors, such as HGF and IGF-1, and angiogenic and mitogenic factors.…”
Section: Stimulation Of Insufficient Liver Regenerationmentioning
confidence: 99%
“…In vitro and in vivo experiments demonstrated that MSCs mainly exert antifibrotic effects by paracrine mechanisms (70). Secretomes or the culture medium of MSCs could also significantly suppress liver fibrosis (71). MSC transplantation could alleviate liver fibrosis and reduce the expression of transforming growth factor-β1 (TGF-β1), Smad2, collagen type I, and α-SMA, and pathological examination showed reduced liver fibrosis areas (72) On the other hand, MSCs can regulate the EMT-MET balance in fibrogenic liver tissue.…”
Section: Mechanism Of the Antifibrotic Effect Of Mscmentioning
confidence: 99%
“…The most effective treatment for end-stage liver disease is orthotopic liver transplantation (OLT). However, its application is limited due to the shortage of organ donors, the high cost and immunosuppression [3,4].…”
Section: Introductionmentioning
confidence: 99%